Importancia del acompañamiento y cuidado de la mujer en el parto humanizado - Quezada Ruiz, Ximena Verenisse (Machala : Universidad Técnica de Machala, 2022)
Humanized childbirth is a process where the woman and family participate with the health professional in the birth of a new being; the objective of the procedure is that it is not traumatic for the woman or her child. Culturally, it was considered that home birth was the best, but due to life risks for the woman as well as the baby, the health center was chosen, this caused the rate of cesarean delivery to rise; it is intended to focus that humanized childbirth is the option and of lower risk, and the participation of women and the family in decisions is relevant. Objective: To analyze the importance of accompanying and caring for women in humanized childbirth, through a systematic review for comprehensive care for women. Materials and methods: A descriptive study was carried out, through a systematic bibliographic review of articles Q1, Q2, and Q3 obtained from databases such as: Cochrane, Pubmed, Scielo and Scopus of the last 5 years. Conclusion: The health professional will have empathy with the woman and will be ready to meet her needs, will be careful, and assertive in pain management. At the time of labor induction, he will provide security by informing about the procedure that he will carry out as a professional, which will generate confidence. Another very important point is family support, the woman will feel protected, accompanied and safe; the woman will cease to be expectant. Keywords: humanized childbirth, maternal care, delivery management, obstetric violence.
El parto humanizado es un proceso donde la mujer y familia participan con el profesional de la salud en el nacimiento de un nuevo ser; el objetivo del procedimiento es que no sea traumático para la mujer ni su hijo. Culturalmente se consideraba que el parto en casa era lo mejor, pero por riesgos de vida para la mujer como el bebe, se optó por el centro de salud, esto provocó que se eleve el índice de parto por cesárea; se pretende enfocar que el parto humanizado es la opción y de menor riesgo, y la participación de la mujer y la familia en las decisiones es relevante. Objetivo: Analizar la importancia del acompañamiento y cuidado de la mujer en el parto humanizado, mediante una revisión sistemática para una atención integral a la mujer. Materiales y métodos: Se realizó Estudio descriptivo, mediante revisión bibliográfica sistemática de artículos Q1, Q2, Y Q3 obtenidos de bases de datos como: Cochrane, Pubmed, Scielo y Scopus de los últimos 5 años. Conclusión: El profesional de la salud tendrá empatía con la mujer y estará presto a las necesidades de la misma, será cuidadoso, y asertivo en el manejo del dolor. Al momento de la inducción del parto dará seguridad informando el procedimiento que como profesional realizará lo que generará confianza. Otro punto muy importante es el acompañamiento familiar, la mujer se sentirá protegida, acompañada y segura; la mujer dejará de ser expectante. Palabras clave: parto humanizado, cuidado materno, manejo del parto, violencia obstétrica.
Keywords: PARTO HUMANIZADO; CUIDADO MATERNO; MANEJO DEL PARTO; VIOLENCIA OBSTÉTRICA